MOLECULAR CHARACTERIZATION OF INDIGENOUS RHIZOBIA NODULATING MEDICINAL LEGUMES USING RAPD METHOD - AMUDHA KUPPUSWAMY,; BABY LENSA TZUDIR,; SRUTHI KRISHNA,; JOYCE PONTES,; SARSHAD,; SELVAM ARJUNAN,; RAJA RAJAN, (International Journal of Pharma and Bio Sciences, 2015)
Rhizobia, gram-negative symbiotic bacteria, play a vital role in natural ecosystems owing to its capability to utilize dinitrogen directly with their nitrogenases. Otherwise, the plants have to get nitrogen in a chemically reduced form, which can be costly. It has been found that both the bacteria and their host plants are involved in determining host specificity. Moreover, the relation between the host plant and the rhizobial bacteria is commonly very specific. Present study deals with the Isolation and Identification of Rhizobium bacteria from root nodules of medicinal legumes, their molecular characterization and determining the genetic diversity among different strains which are isolated. The isolates were identified and characterized on the basis of colony morphology and biochemical traits via Gram Staining, Indole Production, Methyl Red, Voges-Proskauer, Citrate Utilization, Starch Hydrolysis, and Catalase Tests. Random Amplified Polymorphic DNA (RAPD), which can be used as a technique for determining genetic diversity among the bacterial strains isolated, uses short primers with an arbitrary sequence to amplify genomic DNA. In the present study, RAPD analysis was done to investigate the genetic diversity of root nodule organisms isolated from different medicinal legumes. RAPD analysis of genomic DNA of the isolates using 5 random primers such as OPA5, OPA 6, OPA 7, OPW7 and OPW8 yielded banding patterns with each primer. RAPD analysis was done with 5 random primers OPA 5, OPA 6, OPA 7, OPA 06 and OPA 07. Phylogenetic variation was determined by converting RAPD data into a frequency similarity and analysed by Unweighted Pair Group Method with Arithmetic Mean (UPGMA) cluster analysis to produce a phylogenetic tree. RAPD markers revealed possible relationship between host origin, mutation and genetic variation among the isolates. Thus the present study showed that isolate 2 and isolate 3 were most similar species.